Gut microbiota in hepatocellular carcinoma immunotherapy: immune microenvironment remodeling and gut microbiota modification - Mingyao Huang; Quansong Ji; Huiyan Huang; Xiaoqian Wang; Lin Wang (Gut Microbes)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality, with limited treatment options at advanced stages. The gut microbiota, a diverse community of microorganisms residing in the gastrointestinal tract, plays a pivotal role in regulating immune responses through the gut-liver axis. Emerging evidence underscores its impact on HCC progression and the efficacy of immunotherapy. This review explores the intricate interactions between gut microbiota and the immune system in HCC, with a focus on key immune cells and pathways involved in tumor immunity. Additionally, it highlights strategies for modulating the gut microbiota – such as fecal microbiota transplantation, dietary interventions, and probiotics – as potential approaches to enhancing immunotherapy outcomes. A deeper understanding of these mechanisms could pave the way for novel therapeutic strategies aimed at improving patient prognosis.